Trust : knowing when to give it, when to withhold it, how to earn it, and how to fix it when it gets broken - Cloud, Henry (Worthy Publishing, 2023)
"Trust is the fuel for all of life. We are wired biologically, neurologically, emotionally, spiritually, and psychologically to trust. Trust is the currency that drives every relationship, beginning with the foundational bond between infants and their mothers, extending to the trust networks that undergird every human endeavor - art, science, commerce - and binding together every relationship we have ever had or ever will have. Nothing in our world works without trust"--